PENOKOHAN DALAM KUMPULAN CERPEN “SEPOTONG HATI YANG BARU” KARYA TERE LIYE - Maguna Eliastuti; Lina Lina; Runi Ari Wandani; Rizki Daniyanti; Wulandari (Bajang Institute, 2023)
Literary works are born because of something that makes the soul of an author or creator have a certain sense of a problem or event in this world, both what he directly experiences and from the realities of everyday life in society. These problems and events can also affect the characterization of his work. Therefore, the purpose of this research is to identify and analyze the use of characterizations in the short story collection